Recovery of valuable metals from leached solutions of black mass through precipitation method - Natcha Wongnaree; Tanongsak Yingnakorn; Natthicha Ma-Ud; Loeslakkhana Sriklang; Sakhob Khumkoa (Results in Engineering)
The increasing demand for lithium-ion batteries (LIBs) has raised significant concerns regarding the sustainable management of spent batteries, particularly recovering valuable metals. After the separation and leaching of black mass from spent batteries, the resulting pregnant solution served as the initial solution for valuable metals recovery in this investigation. The precipitation-based methods for separating and recovering Al, Ni, Co, Mn, and Li from the pregnant solution were investigated. Initially, Al ions were selectively removed using a NaOH solution, achieving approximately 98.18 % Al removal. Then, Ni, Co, and a part of Mn ions were selectively precipitated using oxalic acid, resulting in the recovery of approximately 99 % of Ni and Co and 84 % of Mn as Ni-Co-Mn oxalate dihydrate compound with a purity of 99.70 %. The remaining Mn ions were then separated using a NaOH solution, precipitating around 99 % of Mn as Mn3O4 with a purity of 96.32 %. Lastly, Li ions were selectively precipitated using disodium hydrogen phosphate, resulting in approximately 83 % recovery as Li3PO4 with a purity of 99.39 %. The comprehensive material balance for the proposed process was also evaluated in this study.